2018
DOI: 10.1007/s00167-018-5274-y
|View full text |Cite
|
Sign up to set email alerts
|

Unloader knee brace increases medial compartment joint space during gait in knee osteoarthritis patients

Abstract: Objectives: Clinical outcome measures suggest the unloader brace provides small-to-moderate improvements in pain and function in varus knee osteoarthritis (OA) patients. However, controversy still exists as to whether the brace has the real effect of increasing tibiofemoral joint space in the medial compartment during functional activity. As a limitation, the previous studies did not report ground reaction forces (GRF) with and without the brace, which could be a confounding factor affecting joint space. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Four studies reported the effects of valgus braces on GRF ( Figure 5(b) ). Three studies found no significant difference between braced and unbraced conditions [ 27 , 33 , 52 ]. However, Schmalz et al [ 38 ] argued that the horizontal force on the arthritic limb was increased by 16.4% BW in brace condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies reported the effects of valgus braces on GRF ( Figure 5(b) ). Three studies found no significant difference between braced and unbraced conditions [ 27 , 33 , 52 ]. However, Schmalz et al [ 38 ] argued that the horizontal force on the arthritic limb was increased by 16.4% BW in brace condition.…”
Section: Resultsmentioning
confidence: 99%
“…Dessinger et al [ 62 ] found that 80% of patients experienced a medial joint space increase of more than 1.0 mm at heel strike, while 65% had a similar change during midstance. Nagai et al [ 52 ] showed that the dynamic space of the medial compartment was significantly increased by 0.3 mm after wearing the brace. In addition, one study [ 63 ] found no significant difference in the separation of the medial and lateral compartments between the braced and unbraced conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In vivo and clinical imaging studies provide support that this mechanism of offloading is valid, though contrasting data have also been reported, 20 such that further validation is necessary. 15,19,21 Other Reported Mechanisms…”
Section: Proposed Unloading Mechanismsmentioning
confidence: 99%
“…These increases in vertical ground reaction force may further load the knee joint and present as jerkier motion, particularly in the frontal plane, as the duration of walking progresses. Larger vertical ground reaction forces and jerkier frontal plane knee motions may load the medial knee joint compartment, increasing the pain and loss of articular cartilage that characterize knee osteoarthritis [118][119][120][121] . Yet, significant increases in jerky knee motion were limited to the frontal plane, despite the fact that individuals reportedly exhibit greater peak sagittal plane knee angles and moments as duration of walking progresses 32,58 .…”
Section: Discussionmentioning
confidence: 99%